ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEBANGKRUTAN DENGAN MENGGUNAKAN MODEL Z- SCORE (STUDI EMPIRIS PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BEI TAHUN 2016-2019 ) - Dwi Saputri; Putu Sulastri (DHARMA EKONOMI, 2022)
ABSTRACTThis study aims to analyze the bankruptcy factors using the Z-Score model with a population of 26 food and beverage companies listed on the IDX in 2016-2019. Sampling technique using purposive sampling method. With a total sample of 13 companies for 4 years so that the research sample is 52 observations. The results of testing hypothesis 1 (H1) show that WCTA has an effect on bankruptcy. Testing hypothesis 2 (H2) shows that RETA has an effect on bankruptcy. Testing hypothesis 3 (H3) EBITTA has an effect on bankruptcy. Hypothesis testing 4 (H4) MVEBVD testing has no effect on bankruptcy. Test 5 (H5) TATO has an effect on bankruptcy. The results of the F test show that the variables WCTA, RETA, EBITTA, MVEBVD and TATO together have an effect on bankruptcy. Keywords : Working Capital to Total Asset, Retained Earning to Total Asset, Earning Before Interest and Tax to Total Asset, Market Value of Equity to Book Value of Debt, Sales to Total Asset, Z-Score ABSTRAKPenelitian ini bertujuan untuk menganalisis faktor-faktor kebangkrutan dengan menggunakan model Z-Score dengan populasi sebanyak 26 perusahaan makanan dan minuman yang terdaftar di BEI tahun 2016-2019. Tehnik pengambilan sampel dengan menggunakan metode purposive sampling. Dengan jumlah sampel sebanyak 13 perusahaan selama 4 tahun sehingga sampel penelitian sejumlah 52 amatan. Hasil pengujian hipotesis 1 (H1) menunjukan WCTA berpengaruh terhadap kebangkrutan. Pengujian hipotesis 2 (H2) menunjukan RETA berpengaruh terhadap kebangkrutan. Pengujian hipotesis 3 (H3) EBITTA berpengaruh terhadap kebangkrutan. Pengujian hipotesis 4 (H4) Pengujian MVEBVD tidak berpengaruh terhadap kebangkrutan. Pengujian 5 (H5) TATO berpengaruh terhadap kebangkrutan. Hasil Uji F menunjukkan variabel WCTA, RETA, EBITTA, MVEBVD dan TATO secara bersama-sama berpengaruh terhadap kebangkrutan. Kata kunci : Working Capital to Total Asset, Retained Earning to Total Asset, Earning Before Interest and Tax to Total Assset, Market Value of Equity to Book Value of Debt, Sales to Total Asset, Z-Score